2021
DOI: 10.7146/se.v10i1.124201
|View full text |Cite
|
Sign up to set email alerts
|

Sound installation art and the intervention of urban public space in Latin America

Abstract: This paper explores the relationship between sound installation art and the appropriation of urban public spaces in Latin America. Latin America is a continent full of contrasts, and in various places throughout the countries, space refl ects the history of each nation through its architecture. We fi nd pre-Hispanic pyramids coexisting with colonial churches and modern buildings. In the last two decades, these sites have been used for purposes other than those for which they were created. On the one hand, thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…These authors argue that the festivity expressed in the daily life of Latin American countries is reflected in several cultural activities in their streets. This generates, they say, ‘complex sonic fingerprints’ (Duarte-García and Wilde 2021: 110), which have a particularity derived from the contrast. The authors propose that such characteristics motivate artists to create sound installations in public spaces where they establish a relationship with sound and social and political space.…”
Section: Sound Installation and Live Codingmentioning
confidence: 99%
“…These authors argue that the festivity expressed in the daily life of Latin American countries is reflected in several cultural activities in their streets. This generates, they say, ‘complex sonic fingerprints’ (Duarte-García and Wilde 2021: 110), which have a particularity derived from the contrast. The authors propose that such characteristics motivate artists to create sound installations in public spaces where they establish a relationship with sound and social and political space.…”
Section: Sound Installation and Live Codingmentioning
confidence: 99%
“…Its main goal is to react to the emotional state of users in order to modify the environment until it reaches the appropriate stage for users to enter the state [3]. Duarte-Garcia and Wilde [4] discussed the relationship between the art of sound installation and the occupation of public space in Latin American cities [4]. It can be found that VR is applied in many display scenes, and some scholars have optimized its display principle, but there is little research on VR communication optimization.…”
Section: Introductionmentioning
confidence: 99%